2005
DOI: 10.1002/pssb.200402121
|View full text |Cite
|
Sign up to set email alerts
|

Moving dislocations in general anisotropic piezoelectric solids

Abstract: The explicit closed-form solution is presented for a moving dislocation with the generalized Burgers vectorin an anisotropic piezoelectric solid, where j D corresponds to an electric dipole layer along the slip plane. The steady-state version of the Stroh formalism for piezoelectricity is used in this work. Particular attention is paid to the basic characteristics of the electric displacement and electric field due to the moving piezoelectric dislocations. As an important example, a detailed analysis is made f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The screw dislocation is assumed to be straight and infinitely long in the z-axis, suffering a displacement jump b = b z and an electric potential jump across the slip plane. The jump in the electric potential corresponds to the electric dipole layer along the slip plane (i.e., Soh et al, 2005). We first discuss the problem within the framework of antiplane shear deformation.…”
Section: Screw Dislocations In Piezoelectric Rodsmentioning
confidence: 99%
“…The screw dislocation is assumed to be straight and infinitely long in the z-axis, suffering a displacement jump b = b z and an electric potential jump across the slip plane. The jump in the electric potential corresponds to the electric dipole layer along the slip plane (i.e., Soh et al, 2005). We first discuss the problem within the framework of antiplane shear deformation.…”
Section: Screw Dislocations In Piezoelectric Rodsmentioning
confidence: 99%
“…The vector function 0 ( ) z f can be easily determined by enforcing the following condition [8] ˆd , d ,…”
Section: Original Papermentioning
confidence: 99%
“…Some errors in the paper of Wu et al [6] were found and corrected by Liu and Fang [7]. The steady-state version of the Stroh formalism for piezoelectricity was employed by Soh et al [8] to derive closed-form solutions for a moving dislocation in an anisotropic piezoelectric solid. Making use of the full dynamic equations of piezoelectromagnetism, Yang [9] analyzed a moving screw dislocation in polarized ceramics.…”
Section: Introductionmentioning
confidence: 97%
“…Yang [9] and Liu, et al [10] considered the problem of a moving dislocation in a magneto-electro-elastic solid. Soh, et al [11] presented an extensive closed-form solution for a moving dislocation in an anisotropic piezoelectric solid. All the above investigations did not consider the influence of interfacial rigid lines (anti-cracks) on moving dislocation.…”
Section: Introductionmentioning
confidence: 99%